Shipping in Inuit Nunangat Governance Challenges and Approaches in Canadian Arctic Waters - Bartenstein, Kristin; Chircop, Aldo (Brill, 2023)
Shipping in Inuit Nunangat is a timely multidisciplinary volume offering novel insights into key maritime governance issues in Canadian Arctic waters that are Inuit homeland (Inuit Nunangat) in the contemporary context of climate change, growing accessibility of Arctic waters to shipping, the need to protect a highly sensitive environment, and the United Nations Declaration on the Rights of Indigenous Peoples. The volume includes policy, legal and institutional findings and recommendations intended to inform scholars and policymakers on managing the interface between shipping, the marine environment, and Indigenous rights in Arctic waters.